Angular correlation measurements of a pair of Lyman-α photons emitted in the photodissociation of H2. (August 2015) - Hosaka, K; Nakanishi, Y; Kogo, R; Schmidt, P; Torizuka, Y; Shigemura, K; Odagiri, T; Knieb, A; Jänkälä, K; Ehresmann, A; Nakano, M; Kumagai, Y; et al.
Synopsis: The angular correlation functions of a pair of Lyman-α photons in the photodissociation of H2 are measured more precisely than in the early experiments [Nakanishi et. al., Phys. Rev. A. 90, 043405(2014)]. The linearly polarized light is used to excite the photodissociation via the doubly excited Q2 1 Π u (1) state.